Islamic working environment, organizational commitment and employee’s job satisfaction and performance in service industry in Malaysia: a conceptual paper / Muhamad Izzuddin Zainudin …[et al.] - Zainudin, Muhamad Izzuddin; Othman, Abdul Kadir; Haji Hassan, Faridah; Ahmad Fadzil, Ahmad Syahmi; Ramdzan, Al-Amirul Eimer (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2018)
This study investigates the role of organizational commitment as a mediator between the Islamic work environment and the employee’s job satisfaction and performance. The study was conducted through the review of previous literature on the variables. It was discovered that previous studies did not include Islamic values as part of their workplace environment framework and only investigate the effect of organizational commitment as the result instead of moderating variable. Thus, a new conceptual model is proposed which will include the Islamic workplace environment as the independent variable, job satisfaction and performance as the dependent variable and organizational commitment as the moderating variable. The model is expected to provide a better understanding to the organization, especially Multinational Corporations (MNC) in understanding the importance of providing Islamic workplace environment for their employees.